Shen-Ling-Bai-Zhu-San Improves Dextran Sodium Sulfate-Induced Colitis by Inhibiting Caspase-1/Caspase-11-Mediated Pyroptosis - Chao, Limin; Li, Zengquan; Zhou, Jiahao; Chen, Wenqian; Li, Yuefei; Lv, Weijie; Guo, Ao; Qu, Qian; Guo, Shining (Frontiers in Pharmacology, 2020)
The traditional Chinese medicine Shen-ling-bai-zhu-san (SLBZS) is described in “Tai Ping Hui Min He Ji Ju Fang.” SLBZS has been shown to be effective against many gastrointestinal diseases. The present study aimed to investigate the effect of SLBZS on experimental colitis in mice and to define the potential mechanisms. Our data suggest that compared to the model group, SLBZS treatment increases mouse body weight and colon length, decreases the DAI score, and improves colonic injury. SLBZS reduces the production of cytokines (IL-1β, IL-18, and TNF-α) in colon tissue and MCME cells. Mechanistically, SLBZS inhibits inflammation by inhibiting the MAPK and NF-κB signaling pathways. Further mechanistic analyses showed that SLBZS attenuates the expression levels of pyroptosis-related genes, including NLRP3, ASC, and GSDMD-N in the colons of mice. In addition, SLBZS restores the levels of the colon tight junction proteins ZO-1 and occludin, suggesting that it protects colonic barrier integrity and ameliorates the progression of colitis. In this paper, we demonstrate that SLBZS attenuates DSS-induced ulcerative colitis injury in mice via the MAPK/NF-κB and pyroptosis signaling pathway. These results indicate that SLBZS is a potential drug for the treatment of UC.